In-silico and in-vitro functional validation of imidazole derivatives as potential sirtuin inhibitor - Dindi, Uma Maheswara Rao; Sadiq, Suhadha Parveen; Al-Ghamdi, Sameer; Alrudian, Naif Abdurhman; Dayel, Salman Bin; Abuderman, Abdulwahab Ali; Shahid, Mohammad; Ramesh, Thiyagarajan; Vilwanathan, Ravikumar (Frontiers in Medicine, 2023)
Introduction: Epigenetic enzymes can interact with a wide range of genes that actively participate in the progression/repression of a diseased condition, as they are involved in maintaining cellular homeostasis. Sirtuins are a family of Class III epigenetic modifying enzymes involved in regulating cellular processes through the removal of acetyl groups from proteins. They rely on NAD+ as a coenzyme in contrast with classical HDACs (Class I, II, and IV) that depend on Zn+ for their activation, linking their function to cellular energy levels. There are seven mammalian sirtuin isoforms (Sirt1-7), each located in different subcellular compartments. Sirtuins emerged as a promising target and inhibitors of natural and synthetic sources are highly warranted. Imidazole derivatives are often investigated as sirtuin regulators due to their ability to interact with the binding site and modulate their activity. Imidazole bestows many possible substitutions on its ring and neighboring atoms, to design and synthesize derivatives with specific target selectivity and improved pharmacokinetic properties, optimizing drug development. Materials and Methods: Ligand preparation, Protein preparation, Molecular Docking, Molecular Dynamics, DFT analysis, and ADME analysis were performed to understand the interacting potential and effective stability of the ligand with the protein. RT-PCR and Western Blot analysis were performed to know the impact of ligands upon the gene and protein expression of Class III HDAC enzymes. Results and Discussion: We evaluated the Sirtuin inhibition activity of our in-house compound comprised of imidazole derivatives by docking the molecules with the protein PDB. ADME properties of all the compounds employed in the study were evaluated, where all the compounds do occur within the favorable range of being a potential drug. The molecule with the highest docking score was analysed using the Density Function theory and that specific compound was used to treat the NSCLC cell lines A549 and NCI- 460. The gene and protein expression data supports the in-silico finding that the compound Ethyl 2-[5-(4-chlorophenyl)-2-methyl-1-H-Imidazole-4-yl) acetate has an inhibitory effect upon nuclear sirtuins. In conclusion, targeting Sirtuins is an emerging strategy to combat carcinogenesis. We present Ethyl 2-[5-(4-chlorophenyl)-2-methyl-1-H-Imidazole-4-yl) acetate possesses a strong inhibitory effect on nuclear sirtuins in NSCLC cell lines.